Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Berbasis Media 3D Page Flip HTML5 MIN 1 Baubau - Lydesty Dahlan; Sulasri; Rusli (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to describe the implementation of learning media based on 3D Page Flip HTML5 and to analyze its effectiveness in improving students' learning outcomes in Islamic Religious Education (PAI) at MIN 1 Baubau. The research employed a Classroom Action Research (CAR) approach conducted in two cycles. The subjects were 19 fifth-grade students. The instruments used included learning outcome tests, observation sheets, and documentation. The results showed that the use of 3D Page Flip HTML5 media successfully increased students' engagement and understanding of the material. In the first cycle, 63.15% of students achieved the Minimum Mastery Criteria (KKM) with an average score of 68.94. After improvements were made in the second cycle, the mastery increased to 89.47% with an average score of 80.52. It can be concluded that the 3D Page Flip HTML5 media is effective in enhancing learning outcomes and is suitable for use in Islamic Religious Education at the elementary school level.